2017
DOI: 10.1111/gtc.12461
|View full text |Cite
|
Sign up to set email alerts
|

Hippo vs. Crab: tissue‐specific functions of the mammalian Hippo pathway

Abstract: The Hippo signaling pathway is a vital suppressor of tumorigenesis that is often inactivated in human cancers. In normal cells, the Hippo pathway is triggered by external forces such as cell crowding, or changes to the extracellular matrix or cell polarity. Once activated, Hippo signaling down-regulates transcription supported by the paralogous cofactors YAP1 and TAZ. The Hippo pathway's functions in normal and cancer biology have been dissected by studies of mutant mice with null or conditional tissue-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 191 publications
(380 reference statements)
0
25
0
Order By: Relevance
“…In an attempt to target CSC-regulating effector molecules, we have focused on YAP1, a principal effector of the Hippo signaling pathway that regulates organ growth in normal tissues. Increasing evidence suggests that YAP1 has diverse roles in tumorigenesis and drug resistance [20], and it has been reported to promote malignant features (e.g., cell proliferation, invasion, migration, and anti-apoptosis) [20,128,129,130,131,132] and drug resistance in various cancers, including breast, bladder and lung cancer (Figure 2) [51,52,133]. Recent studies have also shown that YAP1 contributes to the establishment of an immunosuppressive tumor microenvironment [20].…”
Section: Targeting Cscs By Inhibiting Yap1mentioning
confidence: 99%
“…In an attempt to target CSC-regulating effector molecules, we have focused on YAP1, a principal effector of the Hippo signaling pathway that regulates organ growth in normal tissues. Increasing evidence suggests that YAP1 has diverse roles in tumorigenesis and drug resistance [20], and it has been reported to promote malignant features (e.g., cell proliferation, invasion, migration, and anti-apoptosis) [20,128,129,130,131,132] and drug resistance in various cancers, including breast, bladder and lung cancer (Figure 2) [51,52,133]. Recent studies have also shown that YAP1 contributes to the establishment of an immunosuppressive tumor microenvironment [20].…”
Section: Targeting Cscs By Inhibiting Yap1mentioning
confidence: 99%
“…We previously reported that Mob1a/b null mutant mice succumb to embryonic lethality at embryonic day (E) 6.5 (Nishio et al, 2013). We have also demonstrated that Mob1a/b loss induces extreme hyperactivation of endogenous YAP1/TAZ, resulting in the most severe phenotypes reported among mice mutated in Hippo core components in various tissues (Nishio et al, 2017). Thus, MOB1A/ B is a crucial hub in the Hippo signaling pathway.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, cellular stress signals, [32][33][34][35] as well as metabolism and nutrient signals, [36][37][38][39][40][41] also contribute to the regulation of the Hippo pathway. Disruption of the Hippo pathway causes tissue overgrowth and confers principal features of cancer, [42][43][44] including increased cell proliferation and survival, 45) abnormal cell division, 46,47) and enhanced cell migration. 48,49) In contrast, aberrant activation of the Hippo pathway impairs tissue development, stem cell maintenance, and differentiation.…”
Section: Introductionmentioning
confidence: 99%